Persiapan Pembelajaran Dan Teknologi Untuk Tahun Ajaran Baru Di Era Pandemi Pada Smpit Al Inayah - Syahrizal Dwi Putra (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The COVID-19 pandemic has changed the learning process from face to face to online. Based on IASP 2020, the components of the learning process and the sub-components of learning quality require an active learning process, an assessment of processes and outcomes as well as a remedial and/or enrichment program. Things that need to be prepared in the online learning process in accordance with the quality of learning desired by IASP 2020 and supporting technologies that can be used are video conferencing, Learning Management System (LMS) and Gamification. The results of data collection using questionnaires or questionnaires on participant responses showed positive results where teachers gained knowledge and skills in accordance with the objectives of the activity, namely 80% strongly agreed and 20% agreed.